Performance Evaluation and Analysis Of Unsignaled Interceptions: Case Study: Raya Blega Street-Rajawali Street Bangkalan District - Afada Lazuardi Irhamni; Ibnu Sholichin; Nugroho Utomo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Raya Blega Street intersection is one of the intersections with a relatively high vehicle volume in Bangkalan Regency. There is no APILL (Traffic Signaling Device) available at this intersection, so it has an impact on traffic flow at the intersection. The existence of the market causes many side obstacles which reduce the optimal performance of the intersection. This condition causes the intersection to experience traffic delays, especially during peak hours such as when leaving work or when leaving. In this research, researchers want to identify the problem of congestion at the Raya Blega street-Rajawali street intersection by calculating and analyzing the performance of the Raya Blega street-Rajawali street intersection using the PKJI 2023 method so that it can be used as a benchmark for assessing the performance of unsignalized intersections and assisting related parties in handle problems at the intersection and it is hoped that they can handle the problems that occur at the intersection so that it can create security and safety for passing users.In this study, the highest value was obtained for existing conditions on Monday, April 29 2024, at morning peak hours (07.00-08.00) at approach point A (east Raya Blega street) with an intersection capacity value of 2297,96 smp/hour and the value obtained The degree of saturation is 0,36 and the delay value is 8.44 sec/smp so it is included in Level of Service B. So the status of the Raya Blega street-Rajawali street Bangkalan Regency intersection is still suitable to be maintained.